2016
DOI: 10.1163/15685381-00003031
|View full text |Cite
|
Sign up to set email alerts
|

Species distribution modelling leads to the discovery of new populations of one of the least known European snakes, Vipera ursinii graeca, in Albania

Abstract: Vipera ursinii graeca is a restricted-range, endemic snake of the Pindos mountain range in the southwestern Balkans. The subspecies was previously reported from eight localities in Greece and one locality in southern Albania. We used species distribution modelling based on climate data from known localities in Greece to estimate the potential distribution of the subspecies. The model predicted suitable areas for eleven mountains in southern Albania, which we visited in ten field expeditions in four years. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 35 publications
5
34
0
Order By: Relevance
“…Geographic and taxon sampling. Two samples of V. u. graeca from Albania were included in this study (Mizsei et al 2016), both representing the same mtDNA haplotype as the published sequences from Greece in previous studies (CYT B, ND4;Ferchaud et al 2012). Other specimens investigated were samples representing montane populations of Vipera ursinii macrops (Albania, Montenegro), V. u. ursinii (Italy), V. ursinii ssp.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Geographic and taxon sampling. Two samples of V. u. graeca from Albania were included in this study (Mizsei et al 2016), both representing the same mtDNA haplotype as the published sequences from Greece in previous studies (CYT B, ND4;Ferchaud et al 2012). Other specimens investigated were samples representing montane populations of Vipera ursinii macrops (Albania, Montenegro), V. u. ursinii (Italy), V. ursinii ssp.…”
Section: Methodsmentioning
confidence: 99%
“…Morphological Diagnosis. This taxon differs from all other members of V. ursinii-renardi complex by having the following combination of morphological characters (Nilson & Andrén 1988;Nilson & Andrén 2001;Mizsei et al 2016): small body size (for males a snout to vent length (SVL) max. 40.6 cm, and tail length is 5.4 cm, and for females a SVL max.…”
Section: Systematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Greek Meadow Viper, Vipera graeca (Nilson & Andrén, ), is a poorly known cold‐adapted snake living in alpine meadows between 1,600 and 2,200 m above sea level in the Pindos mountain range in Albania and Greece (Mizsei et al, ). Originally described as a subspecies, molecular studies confirmed the lineage as basal to the entire complex (Ferchaud et al, ; Nilson & Andrén, ) and was subsequently elevated to species level (Mizsei, Jablonski, Roussos, et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Although new techniques for diet tracing (stable isotopes, fatty acid analysis and DNS‐based methods) have advanced considerably recently, visual analysis has several advantages such as the simplicity of sample collection, storage and processing, and the possibility of obtaining information on the species identity, life stage, age or sex of prey and the number and relative abundance of prey consumed, thus still widely used in trophic studies and monitoring programs (Nielsen et al, ). In each population, we intensively searched for snakes (total sampling effort c. 5,700 person‐days) during the vipers’ active season ranging from April to September (Mizsei et al, ). The captured individuals were kept in separate textile bags for 2–4 days (min.…”
Section: Methodsmentioning
confidence: 99%